Fundamentals of urine & body fluid analysis - Brunzel, Nancy A. MS, MLS(ASCP) (St. Louis, Missouri Elsevier, 2023)
Learn how to accurately analyze urine and body fluids with Fundamentals of Urine and Body Fluid Analysis, 5th Edition. Known for its clear writing style, logical organization, and vivid full-color illustrations, this renowned text offers the perfect level and depth of information for understanding the fundamental principles of urine and body fluids frequently encountered in the clinical laboratory. This includes the collection and analysis of urine, fecal specimens, vaginal secretions, and other body fluids such as cerebrospinal, synovial, seminal, amniotic, pleural, pericardial, and peritoneal fluids. Author Nancy Brunzel also shares her extensive knowledge and expertise in the field as she highlights key information and walks you through essential techniques and procedures--showing you how to correlate data with your knowledge of basic anatomy and physiology in order to understand pathologic processes
1. Quality assessment and safety -- 2. Urine specimen types, collection, and preservation -- 3. The kidney -- 4. Renal function and assessment -- 5. Routine analysis-the physical examination -- 6. Routine analysis-the chemical examination -- 7. Routine analysis-the microscopic exam of urine sediment -- 8. Renal and metabolic disease -- 9. Cerebrospinal fluid analysis -- 10. Pleural, pericardial, and peritoneal fluid analysis -- 11. Synovial fluid analysis -- 12. Seminal fluid analysis -- 13. Analysis of vaginal secretions -- 14. Amniotic fluid analysis -- 15. Fecal analysis -- 16. Automation of urine and body fluid analysis -- 17. Body fluid analysis: manual hemacytometer counts and differential slide preparation -- 18. Microscopy
Previous edition: 2018
Includes bibliographical references and index
Keywords: Clinical chemistry; Body fluids -- Analysis; Urine -- Analysis